REMOTE SENSING AND GIS FOR LAND COVER CLASSIFICATION AND CHANGE DETECTION IN GAZIPUR SADAR, BANGLADESH DURING 1973-2017 - Md Arafat Hassan; Rakibul Islam; Rehnuma Mahjabin (Geoplanning: Journal of Geomatics and Planning, 2018)
RETRECTED BY EDITOR